Aplikatif Manajemen Pendidikan dalam Pembentukan Karakter Santri: Studi PP. Sirojul Hasan Klenang Kidul Probolinggo - Rizqi Fauziyah; Nanang Qosim (LP3M Universitas Islam Zainul Hasan Genggong, 2020)
Students character education planning is carried out by boarding school (kyai) caregivers, educator, and the preparation of the determination of needs, program design, regarding targets/targets, location, time and program applications in the entity. Managing and caring for educational sarpras is a shared responsibility, starting from the caregiver of boarding school (kyai), the asatidz-asatidzah, santri, committees and neighboring pesantren. Coordination of the development of santri character education is carried out in guidance with appropriate educator. application of students through various learning models, habituation, exemplary/role models, civilizing discipline (discipline culture), tazkiyyatun annafsi (self-cleansing, soul and heart), motivation and order Assessment of character education can be through examinations written, report cards, behavior (good morals), sympathizers, graduates, and public.